Digital Marketing Strategy of Creative Consultant during COVID-19 Pandemic: a Qualitative Approach - Karerin Narisa Putri; Daniel Hermawan (International Journal of Entrepreneurship, Business, and Creative Economy, 2021)
In this research, we aim to explain how creative consultant use digital marketing and the success rate of this marketing strategy, since the digital marketing has improved business strategies to increase productivity and sales, especially during COVID-19 pandemic. Our study used qualitative method and we conduct interview and observation to collect the data. In this study, we use several analysis tools, such as EFE, CPM, IFE, SWOT, SPACE, IE, and QSPM, and our results showed that digital marketing strategy is quite effective from the point of view of promotional and advertising strategies carried out, even though not giving maximum profit as in pre-pandemic. Henceforth, creative consultant needs to use a market penetration strategy to improve their business performance.